2006
DOI: 10.1590/s0034-72992006000400013
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização clínica de idosos com disfunção vestibular crônica

Abstract: Di zziness is common among the elderly. Aim: To characterize social, demographic, clinical, functional and otoneurological data in elderly patients with chronic vestibular disorder. Method: A sequential study of 120 patients with chronic vestibular disorder. Simple descriptive analyses were undertaken. Results: Most of the patients were female (68.3%) with a mean age of 73.40±5.77 years. The average number of illnesses associated with the vestibular disorder was 3.83±1.84; the patients were taking on average 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
29
1
26

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 9 publications
9
29
1
26
Order By: Relevance
“…Moreover, mortality rates grows with age, thus reducing the number of elderly diagnosed with vestibular dysfunction as age advances 13 . In this study, most participants were women (80%), which is in agreement with reports found in the literature [14][15][16] . Dizziness is more frequently found among women, at the rate of 2:1.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, mortality rates grows with age, thus reducing the number of elderly diagnosed with vestibular dysfunction as age advances 13 . In this study, most participants were women (80%), which is in agreement with reports found in the literature [14][15][16] . Dizziness is more frequently found among women, at the rate of 2:1.…”
Section: Resultssupporting
confidence: 93%
“…with regard to falls, 64 of the elderly individuals (53.3%) had fallen at least once during the preceding year, and 35 (29.2%) reported recurrent falls. The full sociodemographic, clinical-functional and otoneurological characterization of the sample was described in an earlier paper 6 .…”
Section: Resultsmentioning
confidence: 99%
“…The psychosomatic consequences of dizziness caused by vestibular disorders may include anguish, anxiety and panic attacks, fear of going out alone, interference in daily activities, feelings of being outside of reality, depersonalization and depressed mood [3][4][5][6] .…”
mentioning
confidence: 99%
“…Complete otoneurological, clinical-functional and socio-demographic information of this sample is described in another publication 21 . We noticed a week negative statistically significant correlation between BBS score and patient age (ρ= -0.354; p<0.001).…”
Section: Resultsmentioning
confidence: 99%